Analysis of Compliance with the Use of Personal Protective Equipment among Cleaning Service Officers at Palembang Bari Regional Hospital, Palembang City (HEALTH CARE: JURNAL KESEHATAN, 2024)
Background: The importance of using Personal Protective Equipment (PPE) in reducing the risk of work accidents and occupational diseases, especially for cleaning workers at Palembang BARI Regional Hospital who are vulnerable to infectious diseases such as HIV and tuberculosis, encourages the need for research to evaluate their practice of using PPE. The purpose of this research is to determine the analysis of compliance with the use of personal protective equipment among cleaning service officers at Palembang BARI Hospital, Palembang City in 2024. Method: This research is a quantitative research with a cross-sectional study design. The sample was 56 cleaning service officers at Palembang BARI Hospital, Palembang City. Analysis uses univariate, bivariate methods with the chi-square test, and multivariate analysis. Results: Compliance in the use of PPE is related to the availability of adequate PPE and K3 standards. There is a relationship between compliance with the use of PPE and gender, knowledge, attitudes, availability of PPE, and supervision. However, there is no relationship between compliance and age, education, length of service, comfort of PPE, training, and regulations. The results of multivariate analysis show that the most dominant variable is the availability of personal protective equipment (PPE) with an OR of 28.75. This means that respondents who stated that there was no availability of PPE were 28.75 times more likely to be non-compliant with the use of PPE compared to respondents who stated that there was availability of PPE. Conclusion: Availability and easy access to obtain PPE can increase compliance with its use.